2000
DOI: 10.1016/s0002-9440(10)64595-6
|View full text |Cite
|
Sign up to set email alerts
|

Up-Regulation of Galectin-3 in Acute Renal Failure of the Rat

Abstract: Galectin-3, a multifunctional beta-galactoside-binding lectin, is known to participate in development, oncogenesis, cell-to-cell attachment, and inflammation. We studied to determine whether galectin-3 is associated with cell injury and regeneration in two types of acute renal failure (ARF), namely ischemic and toxic ARF. In ischemia/reperfusion renal injury in rats (bilateral renal pedicles clamped for 40 minutes), galectin-3 mRNA began to increase at 2 hours and extended by 6.2-fold at 48 hours (P: < 0.01 ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
89
1
4

Year Published

2001
2001
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(99 citation statements)
references
References 46 publications
5
89
1
4
Order By: Relevance
“…Their upregulation was detected as early as within a few hours and returned to baseline within 1 d. These are considered the early response genes to renal injury. The increase in gene expression of Pax-2 (8,11), activin-A (10), platelet-derived growth factor (PDGF) (32), ciliary neurotrophic factor (CNTF) (33), hepatocyte growth factor receptor (c-Met) (34), galectin-3 (35), and transforming growth factor-␤1 (TGF-␤1) (36) persisted for several days, and these genes are thought to be responsible for tubular regeneration. The upregulation of LIF was observed on 1 d after the ischemic insult and persisted for 7 d. Its time course suggests that LIF participates in the regeneration process.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their upregulation was detected as early as within a few hours and returned to baseline within 1 d. These are considered the early response genes to renal injury. The increase in gene expression of Pax-2 (8,11), activin-A (10), platelet-derived growth factor (PDGF) (32), ciliary neurotrophic factor (CNTF) (33), hepatocyte growth factor receptor (c-Met) (34), galectin-3 (35), and transforming growth factor-␤1 (TGF-␤1) (36) persisted for several days, and these genes are thought to be responsible for tubular regeneration. The upregulation of LIF was observed on 1 d after the ischemic insult and persisted for 7 d. Its time course suggests that LIF participates in the regeneration process.…”
Section: Discussionmentioning
confidence: 99%
“…The expression pattern of galectin-3 is similar to that of LIF. Galectin-3 is expressed in ureteric bud-derived structures in fetal and adult kidney and re-expressed in injured proximal tubule cells (35,38). One hypothesis to explain the re-expression in cells of different origin in disease is that the regenerating proximal tubule cells are dedifferentiated and have different characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…Galectin-3 mRNA expression in renal tubules was shown to be upregulated early after IRI and toxin-induced AKI and persisted for 7 days following injury [9]. Importantly, galectin-3 has been implicated in the development of myocardial fibrosis and heart failure in an experimental model of AKI [10].…”
Section: Pathophysiologic Mechanisms Of Aki-induced Cardiac Injurymentioning
confidence: 99%
“…The strongest evidence of a cardiorenal link between AKI and the development of cardiac fibrosis is the β-galactoside-binding lectin galectin-3 [9,10]. Galectin-3 mRNA expression in renal tubules was shown to be upregulated early after IRI and toxin-induced AKI and persisted for 7 days following injury [9].…”
Section: Pathophysiologic Mechanisms Of Aki-induced Cardiac Injurymentioning
confidence: 99%
“…One group studied two models of AKI in the rat (ischemic and nephrotoxic) and found that galectin-3 was intensely upregulated and prevented chronic tubular injury by limiting apoptosis, enhancing matrix remodeling and attenuating fibrosis [66]. However, another group using an ischemiareperfusion model in wild-type versus knockout mice demonstrated that in early AKI the knockout mice seemed protected, with lower levels of interleukin-6, fewer ROS, less macrophage infiltration and lower peak concentrations of urea [67].…”
Section: Galectin-3mentioning
confidence: 99%